Analysis of environmental sustainability of European Union member states using AHP-TOPSIS methods according to world development indicators - Ezgi Güler (Environmental Research Communications)
Environmental sustainability has become a pressing policy issue for the European Union (EU), yet robust, comparative evaluations among member states remain limited. This study addresses this gap by proposing a Multi-Criteria Decision Making (MCDM) framework to assess the environmental sustainability performance of 27 EU countries. The objective is to generate a reproducible and data-driven ranking that can inform policy decisions at both national and EU levels. Six environmental criteria, based on World Bank’s World Development Indicators, are weighted using the Analytical Hierarchy Process (AHP). These weights are then integrated into the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) to construct a sustainability ranking using real-world data from 2024. To explore the methodological impact of distance measures within TOPSIS, three variants—Euclidean, Manhattan, and Chebyshev—are applied. A key contribution of this research is the sensitivity analysis that examines how different distance measures affect country rankings. This analysis, rarely explored in prior literature, is conducted using Spearman’s rank correlation coefficients to assess the robustness of results. Findings reveal that the Manhattan distance measure produces more stable rankings across the criteria. The study provides a methodological advancement by linking expert-based weighting with distance-based MCDM, offering practical insights for environmental policy development within the EU.